The Impact of the Transport Road Network on the Development of Tourist Sites in Al-Qadisiyah Governorate - Salem, Hayder Abdul Kareem (Thi Qar Arts Journal, 2024)
The road network is one of the most important components of infrastructure in the development and enhancement of tourist sites due to its vital role in stimulating tourism worldwide. As the transport sector develops, it directly contributes to the prosperity of tourism. Conversely, the absence of suitable transportation reduces the significance of tourist sites and limits their attractiveness to tourists. This highlights the importance of the road network and its direct impact on the development and sustainability of tourist sites. This research aims to study the developmental potentials of Al-Qadisiyah Governorate, focusing on transport infrastructure and its impact on tourism activity in the region. The study showed that the governorate possesses abundant natural and human resources, but suffers from weak investment and sustainable development. The distribution of the population and its relation to road networks was analyzed, revealing that areas with high population density have more developed transport networks. The results indicated that the road network is insufficient, with a density of 4.3 km per 10,000 people, which is low compared to national averages. Additionally, most roads lack essential services such as rest stations, health facilities, and emergency services, negatively affecting road usage. The study also revealed severe neglect of archaeological sites, particularly in terms of the necessary infrastructure to support tourism, such as hotels and paved roads. Based on these results, the research recommended the urgent implementation of developmental plans aimed at improving transportation infrastructure and enhancing tourism by developing service facilities and improving road quality to raise the level of economic and tourism development in the governorate.